Structural and passive mechanical properties of the medial gastrocnemius muscle in ambulatory individuals with chronic stroke. (June 2022) - Huang, Meizhen; Miller, Tiev; Fu, Siu Ngor; Ying, Michael T.C.; Pang, Marco Y.C.
Abstract: Background: This study aimed to investigate the structural, morphological and passive mechanical properties of the medial gastrocnemius muscle among ambulating chronic stroke survivors using a computational model previously established in healthy individuals without stroke. Methods: Individuals with chronic stroke ( n  = 14, age = 63.4 ± 6.0 years) and healthy controls ( n  = 15, age = 59.6 ± 8.4 years) participated in the study. The mechanical properties of the medial gastrocnemius were measured during continuous passive ankle motion using ultrasound elastography and a corresponding muscle mechanical property-angle curve was estimated where slack angle and elasticity were determined. Muscle thickness, fascicle length, pennation angle, and echo intensity were also assessed using B-mode ultrasound. Findings: No significant differences in slack angle (paretic: −16.2° ± 6.13°, non-paretic: −16.93° ± 6.80°, p  = 0.82), or slack elasticity (paretic: 4.36 ± 1.94 kPa, non-paretic: 4.54 ± 1.24 kPa, p  = 0.64) were found between sides or groups. Lower muscle pennation angle (paretic: 13.6 ± 2.9°, non-paretic: 15.9 ± 2.0°, p  = 0.019) and higher echo intensity (paretic: 80.5 ± 13.6, non-paretic: 63.4 ± 17.1, p  = 0.003) were observed for paretic muscles. No significant between-sides differences were found for muscle thickness (paretic: 1.5 ± 0.3 cm, non-paretic: 1.6 ± 0.2 cm, p  = 0.255) or fascicle length (paretic: 6.6 ± 1.9 cm, non-paretic: 7.1 ± 2.2 cm, p  = 0.216). Significant between-groups difference was also observed for fascicle length [non-dominant side (control): 6.2 ± 0.8 cm, paretic side (stroke): 6.6 ± 1.9 cm, p  = 0.017]. Interpretation: Although muscle mechanical properties increased exponentially over the slack ankle, measures between paretic and non-paretic sides were similar in ambulating participants with chronic stroke. Side-to-side differences in structural and morphological measures suggest the impact of stroke was relatively more pronounced for these muscle parameters than for passive mechanical properties. Highlights: Computational estimation of the shear modulus-angle curve is feasible post-stroke. No within- or between-group differences were found for muscle mechanical properties. Structural and morphological muscle properties showed between-sides differences.